O conteúdo curricular da sociologia no ensino médio a partir dos planos de aulas dos professores das escolas públicas de Fortaleza - Ribeiro, Josenira Unias (2020)
The discipline of Sociology in the school context of High School was consolidated as mandatory in the curriculum of schools, after Federal Law No. 11,684 of June 2, 2008. Period that has already changed the scenario of Teaching Sociology: growth in the training of teachers in Graduation; the inclusion of books in the National Textbook Program, as well as the growing number of studies and scientific productions on the discipline. The objective of this work is to analyze the lesson plans of Sociology teachers and map the contents that are chosen for the three grades of high school. The field of study of this research took place with the teachers who work in the state public schools of Fortaleza, having as some of our references the authors who are analyzing the curriculum of Sociology in schools, such as: Anita Handfas, Ileizi Fiorelli, Flávio Sarandy, Cristiano Bodart and Simone Meucci. A documentary and bibliographic research was carried out, gathering information on legislation, articles and authors that contributed to the methodological path and reflections. Through the analysis of the lesson plans it was possible to identify that the sociological contents, the textbooks and the methodologies used in the elaboration of the lesson plans influence in their teachers' choices. Thus, it was possible to verify significant differences in the curricular content of high school offered to high school students within the same grade